Multi-criteria method for reducing risks in strategic decisions for new businesses in the wood industry - Saick, Esther Krause; Deud, Rafael Bottacine Amed; Rodrigues, Thiago de Almeida; Torres, Henrique Bertochi (Brazilian Journal of Production Engineering, 2026)
The timber sector is growing in Brazil and worldwide, driven by demand from the construction, furniture, and packaging industries. In the state of Espírito Santo (ES), this sector accounts for 25% of the agribusiness GDP and faces production bottlenecks due to limited planted area. Given the sector’s economic relevance and the uncertainties involved in the development of new ventures, it becomes essential to adopt strategic decision support approaches. This study aims to investigate how Multicriteria Decision Aid (MCDA) methods can be applied to the management of strategic risks related to the implementation of new sawmills. To this end, a case study was conducted in the municipality of Venda Nova do Imigrante (ES), using the FITradeoff method to support two decisions: selecting the location for the facility and choosing the most appropriate production line. The results indicated that Site A and Line 2 were the most advantageous alternatives, with the criteria “land price” and “number of jobs generated” standing out in the decision hierarchy. Sensitivity analysis indicated robustness in the recommendations. It is concluded that the proposed approach contributes to reducing strategic uncertainties by supporting structured decision-making in new ventures within the timber sector.